Effect of carbon alloying on hydrogen embrittlement of a Cantor alloy - Panchenko, M. Yu; Melnikov, E. V.; Gurtova, D. Yu; Astafurova, Elena G. (Письма о материалах)
We have investigated the effect of hydrogen-charging on the mechanical properties and fracture mechanisms of high-entropy alloys Fe20Mn20Cr20Ni20Co20 and Fe20Mn20Cr20Ni20Co19C1 (at.%). Both alloys have a coarse-grained single-phase face-centered cubic (fcc) structure. It was found that doping with carbon decreases the content of hydrogen absorbed by the specimens during electrochemical hydrogen-charging (in a 3 % NaCl water solution, at j =10 mA / cm2 for 50 h): 134 wppm and 63 wppm for carbon-free and carbon-doped alloy, respectively. Hydrogen-charging contributes to an increase in the yield strength and a decrease in the ductility of the alloys. Despite the lower concentration of dissolved hydrogen, the hydrogen-associated solid-solution strengthening of the carbon-doped alloy is higher than that in the interstitial-free alloy. The hydrogen embrittlement index, IH =17 %, for carbon-alloyed specimens is lower than IH = 25 % for interstitial-free specimens. In both alloys, the hydrogen-affected surface layers of the specimens fracture in a similar brittle mode — intergranular fracture dominates.